Exploratory study on the use of services and information products circulation units and reference Library Health Sciences at the University of Costa Rica - Pérez Solano, Melania (2013)
This document summarizes the final graduation work on the use of the information services of the circulation and reference units of the Health Sciences Libraries of the University of Costa Rica. In the first instance, there is a brief contextualization of the quality of library information by gathering different types of data from different institutions. As a second section, the general and specific objectives that structured the research appear; to later refer to the methodological procedure. Finally, the conclusions and recommendations resulting from the research findings are shown.